The Meaning and Functions of Sarcasm and Humour in Gen Z Netizens’ Comments on Viral Issues on TikTok: A Pragma-Semantic Analysis - Isti Qomatusadiah Fimulkillah; Nurrifani Nurrifani; Najwa Riskiyani; Tatu Siti Rohbiah (Journal of English Language Teaching, Linguistics, and Literature (JETLEE), 2026)
The increasing use of sarcasm and humour in social media discourse has transformed online comment sections into significant spaces for social criticism and public engagement. The present study investigates the use of sarcasm and humour by Generation Z (Gen Z) netizens on TikTok from a pragma-semantic perspective, focusing on their responses to viral issues during 2025–2026. It examines how sarcastic and humorous expressions function not only as forms of entertainment but also as vehicles for criticism, resistance, and evaluation in contemporary digital communication. Employing a qualitative content analysis to examine 20 TikTok comments selected from five viral topics. The analysis was guided by Austin’s (1962) dan Searle’s (1969) Speech-Act theory and a pragma-semantic framework, which integrates semantic meaning with contextual interpretation to uncover the pragmatic functions of sarcasms ang humour. The findings reveal a functional shift in online language use, in which TikTok comments serve not merely locutionary purposes of information sharing but also illocutionary functions of criticism, satire, and social resistance. Gen Z users frequently employ indirect speech, absurd humour, irony, wordplay, and (clumsy) metaphors to express scepticism toward public figures, institutions, and policies. Furthermore, conventional expressions such as “thank you” undergo semantic-pragmatic shifts, functioning sarcastically in specific contexts. The findings demonstrate that humour and sarcasm have become strategic communicative resources through which Gen Z articulates social criticism, negotiates public issues, and actively participate in contemporary digital discourse.